Trainee Responses to Hurricane Harvey: Correlating Volunteerism With Burnout - Yeo, Crystal Jing Jing; Román, Gustavo C.; Kusnerik, David; Burt, Trevor; Mersinger, Dottie; Thomas, Shaylor; Boone, Timothy; Powell, Suzanne Z. (Frontiers in Public Health, 2018)
Background: Natural disasters take a heavy toll not only on their victims, but also on physicians who suffer vicarious trauma and burnout. New trainees in Houston, from entering PGY1 residents to entering fellows, underwent even more upheaval and stress during Hurricane Harvey. Many responded to calls for volunteer help. Objective: To investigate the impact of Hurricane Harvey on new trainees at our institution, and correlate volunteerism with measures of burnout and resilience. Methodology: Thirty three new trainees out of 90 (43% of population) from all specialties in our institution voluntarily responded to an online survey on the impact of Hurricane Harvey on their lives, whether or not they volunteered and in what form, and answered questions drawing from the abbreviated Maslach burnout survey and Resiliency Quiz. Statistical analyses were conducted using GraphPad Prism and Excel data analysis. Results: The top areas impacted were emotional health (32%), eating habits (29%), family (25%) and finances (25%). The main voluntary activities were covering for colleagues who could not make it to hospital (50%), donating money and supplies (36%), and cleaning and rebuilding (36%). Volunteering was associated with feelings of appreciation (76%), happiness (62%), thankfulness (57%), purposefulness (43%) and pride (33%). Fewer volunteers scored lowly in personal achievement as compared to non-volunteers (10 vs. 38%, p = 0.05). Significance: Hurricane Harvey affected health, finances and family of new trainees, more than half of whom volunteered to help. Volunteers had a greater sense of personal achievement as compared to non-volunteers. This may be due to having more volunteers among less burnt-out trainees or because volunteering reduced burnout and stress responses/trauma. These results suggest that volunteer opportunities should be made available in programs targeting resident burnout.